Co-existent cristobalite and iridium at 65 Ma, Anjar Intertrappeans, Kachchh, western India - SANT, DA; MATHEW, G; KHADKIKAR, AS; GOGTE, V; GUNDURAO, TK (Cretaceous Research, 2003)
Cristobalite (a high-temperature low-pressure silica polymorph) is reported for the first time from the 65 Ma Anjar intertrappean deposits. It is characterized by a sharp, intense peak (X-ray diffraction) at d-spacing value 4.055Angstrom, followed by a moderate peak at 2.489Angstrom. Its presence is confirmed through Fourier Transform Infrared spectroscopy with absorption bands at 620 and 380 cm(-1). The distribution of volcanic cristobalite coincides with the distribution of iridium in the deposits. When taken in tandem with the absence of shocked quartz, spinels, stishovite and other signatures of an impact origin, this co-existence suggests that the iridium at Anjar is probably of volcanic origin. (C) 2003 Elsevier Ltd.